Surgical Lip Repositioning Procedure for the Reconstruction of Pink Esthetics in a Periodontal Way: A Case Report - Dr. Manohar Laxmanrao Bhongade, Dr. Bushra K, Quazi; Sehdev, Dr. Bhumika (International Journal of Innovative Research in Medical Science, 2017)
Cosmetic procedures involving reconstruction of gingivae have become an integral part of current periodontal practice. The ability to cover unsightly exposed teeth and recontour soft tissue by reducing the excessive gingival display have added an esthetic angle to the traditional concept of biological and functional periodontal health. Excessive gingival display can be managed by a variety of treatment modalities, depending on the specific diagnosis. Lip repositioning surgery is a largely unknown and underutilized treatment modality for excessive gingival display. Lip repositioning is a simple non-invasive surgical procedure to treat ‘gummy smile’. It restricts the muscle pull of the elevator lip muscles thereby reducing the gingival display while smiling. This procedure is safe and predictable with minimal risk or side effects. The aim of the present case report was to minimize excessive gingival display with a lip repositiong procedure; thereby reconstructing the pink esthetics in a periodontal way. The lip repositioning technique to decrease the amount of gingival display proved to be more conservative and provided good esthetic outcome.